The Effect of the Quiet Eye Training on the Gaze Control in Pistol Shooters: Randomized Control Trial - Jaleh Bahramian-Dehkordi; Saleh Rafiee; Jaleh Bagherli; Sayed Mohammadkazem Vaezmousavi (Vesnu Publications, 2020)
Introduction: the aim of this study was to investigate the effect of quiet eye training on gaze control in pistol shooters.Materials and Methods: This study was a controlled clinical trial in which 20 shooters with an average age of 22 years and a record of 545-555 m were selected using the purposive and convenience sampling method and assignied to two groups of quiet eye and technical training (10 people in each group) using the ranked pre-test scores (ABBA method). The participants performed the pre-test, post-test, and retention tests. The quiet eye test of the training group was performed with the elite shooter pattern along with verbal instructions in eight sessions and six blocks of 10 consecutive shots. Data was analyzed through independent t-test, repeated measures analysis of variance (ANOVA), and Bonferroni post hoc test (α = 0.05).Results: The mixed ANOVA test results showed that for the variable of the total duration of quiet eye, the main effect of the stage, the main effect of the group, and the interactive effect of the stage and the group were significant (P = 0.001); Only the effect of group (P = 0.002) was significant for the variable of onset. Regarding the quiet eye offset variable, the main effects of the stage and the group and the interaction effect of the stage and the group (P = 0.001) were significant. Repeated measures ANOVA indicated that changes in quiet eye timing were significant for the quiet eye training group (P = 0.001). Given the result of the Bonferroni post hoc test, the quiet eye training group in the post-test (P = 0.001), retention (P = 0.003), and post-test and retention (P = 0.001) stages compared to that of the pre-tests had longer total duration and offset of quiet eye. The esults of the independent t-test of quiet eye training group in the post-test (P = 0.004) and retention (P = 0.002) and post-test and retention (P = 0.001) stages compared to the technical training group had better total duration and offset of quiet eye.Conclusion: Quiet eye training may influence proper timing of quiet eye through external visual attention and improve the gaze control of pistol shooting skills.